Interaction of lipopolysaccharides and lipid A with complement in rats and its relation to endotoxicity. - Freudenberg, M A (1978)
Uniform salt forms of endotoxic lipopolysaccharides (LPS) and free lipid A showing distinct differences in their anticomplementary activity, as well as a nontoxic LPS, are used in a new approach of studying the role of complement in endotoxin shock. The use of these defined LPS forms led to the identification of two timely, distinct depressions in complement hemolytic activity after administration of endotoxin in rats. An early depression occurred within 10 min after injection, and a late one developed more gradually, with lowest values at 6 to 9 h. The early depression represents a direct interaction of LPS with complement. It was obtained by toxic and nontoxic preparations that exhibit a high molecular weight and anticomplementary activity in vitro. The early depression was not related to the toxic properties of the LPS. The late depression was obtained only with endotoxically active LPS in lethal and 100-fold-lower concentrations, regardless of their molecular weight and of their in vitro anticomplementary activity.